The Influence of the Antecedents of SCQRM Implementation on Organizational Performance with the Moderating Role of Organizational Culture in the Indonesian Navy - Yohannes Enggar Riyadi; Lucy Warsindah; Agus Adriyanto; Dangan Waluyo (Business and Entrepreneurial Review, 2021)
This study aims to determine the effect of the antecedents of Supply chain quality risk management (SCQRM) implementation on organizational performance with the moderating role of organizational culture in the Indonesian Navy. Based on data from questionnaire survey data totaling 260 Indonesian Navy officers, the SCQRM theory model is proposed and the structural equation model is used to test the proposed hypothesis. The results show that strategic leadership, information, and control mechanisms are significant antecedents of SCQRM implementation. Furthermore, strategic leadership and information significantly contribute to organizational performance. An interesting finding is that control mechanisms do not have a direct impact on organizational performance, but they do contribute indirectly to organizational performance mediated by SCQRM implementation. Also, SCQRM implementation significantly contributes to organizational performance and the moderating effect of organizational culture strengthens the relationship between SCQRM implementation and organizational performance. This study focuses on the concept and implementation of SCQRM in Indonesian Navy logistics with the role of strategic leadership, information, control mechanisms, and organizational culture to improve organizational performance using single respondents and expert perceptions, namely Indonesian Navy Officers. The managerial implications suggest that complementary benefits arise from the adoption of a more holistic approach to the management of supply chain quality risk at the organizational level with supported the role of strategic leadership, information, control mechanisms, and organizational culture will improve organizational performance. Three contributions to science in the development of SCQRM theory. First, this study develops an SCQRM theoretical model with three unique dimensions (supplier development, risk management integration, and proactive product recall). Second, this study provides a new perfection of how the complementarity system of SCQRM is operated to improve organizational performance. Moreover, the findings imply that a successful SCQRM implementation is built on a complementarity power in risk management resources and routines. The multiple manifestations of the three SCQRM dimensions are all driven by a cohesive, yet unobserved synergy, which also forms one of the competencies of the organization. Third, this study also provides a new perfection on the role of strategic leadership, information and control mechanisms as antecedents of SCQRM implementation, and the moderating role of organizational culture that strengthens the relationship between SCQRM implementation and organizational performance.